Politics, religion and ideas in seventeenth- and eighteenth-century Britain : essays in honour of Mark Goldie - Champion, Justin; Coffey, John, 1969-; Harris, Tim, 1958-; Marshall, John, 1961- (Studies in early modern cultural, political and social history ;, 2019)
This volume traces the evolution of Whig and Tory, Puritan and Anglican ideas across a tumultuous period of British history, from the mid-seventeenth century through to the Age of Enlightenment.